Factors associated with the use of medicines and self-medication during the COVID-19 pandemic in 12 Latin American countries - Mejia, Christian R. (2024)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has triggered a rise in the global phenomenon of self-medication. The use of medicines with unsubstantiated claims of benefit for the prevention and/or treatment of infected people has been widely adopted. Objective: To determine the factors associated with the use of medicines and self-medication by Latin American populations during the COVID-19 pandemic. Methods: This analytical cross-sectional study was conducted via an analysis of secondary data collected from 8777 responses from 12 Latin American countries obtained from a survey on the use of medicines and self-medication during the pandemic. Results: Respondents who reported using Paracetamol, Ibuprofen, or antibiotics (ABx) disclosed this as self-medication in 26.9%, 16.6%, and 9.7% of cases respectively. In our multivariate analysis, significant associations were found between: self-medication by individual choice and the use of Hydroxychloroquine, ABx, or non-steroidal anti-inflammatory drugs (NSAIDs) (p = 0.026, = 0.003, and <0.001 respectively); self-medication on the recommendation of a family member, with ABx, Paracetamol, Ibuprofen, or other NSAIDs (p <0.001, <0.001, <0.001, and <0.001 respectively); and self-medication on the recommendation of another person, with Chloroquine, Hydroxychloroquine, Azithromycin, Penicillin, other ABx, Warfarin, Ivermectin, Paracetamol, Ibuprofen, or other NSAIDs (p <0.001, <0.001, <0.001, = 0.001, <0.001, <0.001, = 0.004, <0.001, <0.001, and <0.001 respectively). Conclusion: There was a significantly high prevalence of self-medication in our Latin American study population, including the use of medicines not recommended for COVID-19 treatment and/or prevention. The implementation of public health measures aimed at combating the worrying COVID-19 infodemic is essential to prevent this ongoing issue and its associated negative impacts on both current public health and future medication efficacy. This is especially important in the case of ABx due to the threat of a future antimicrobial resistance pandemic.